FORMULASI TERIGU DAN TEPUNG KELADI PADA PEMBUATAN ROTI TAWAR - Bramtarades, I Gusti Putu Bayu; Putra, I Nengah Kencana; Puspawati, Ni Nyoman (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2013)
This research aims to investigate the effect of formulations of wheat and cocoyam flour used in bread making and to know the comparison of wheat and cocoyam flour that produce bread with good characteristics. This research used Randomized Block Design with a comparisons of wheat and cocoyam flour as follows: 100% : 0%, 95% : 5%, 90% : 10%, 85% : 15%, 80% : 20%, 75 % : 25% and 70% : 30%. The treatments was repeated twice, so there were 14 experiment units. The data was analyzed by analysis of variance, if there were significant effects then followed by Duncan's test. Result of the research shown that formulation of wheat and cocoyam flour on the bread making had significant effects on bread volume, water content, ash content, crude fiber content, protein content, fat content, flavor, color, texture and overall acceptance, but had not significant effects on taste and pores uniformity of the bread. The formulation of 85% wheat and 15% cocoyam flour, produced bread with good characteristics by: swelling degree of 129.87%; water content of 32.13%, ash content of 1.43%, protein content of 16.42%, fat content of 10.09%, crude fiber content of 6.33%, carbohydrate content of 39.92%, pores uniformity of bread was mostly uniform, color was mostly liked, flavor was mostly liked, taste was mostly liked, texture was mostly liked, and overall acceptance was mostly liked.
Keywords: wheat, cocoyam flour, bread